Knowledge Sharing between Marketing and Accounting from a Coopetitive Perspective: Empirical Evidence from Vietnam - Nguyen, Phong Nguyen (University of Economics Ho Chi Minh City, 2023)
This study examines cross-functional knowledge sharing at the interface between marketing and accounting departments within business organizations. It develops a coopetition model to examine the effects of contingent variables including cross-functional competition and organizational innovativeness on the coordination–sharing–performance (C–S–P) link. The results obtained from a survey of 178 large firms in Vietnam demonstrate that except formalization all coordination mechanisms including lateral relations, informal networking, and shared visions have positive influences on the knowledge sharing at the interface between marketing and accounting departments. Moreover, competition between these moderates the effects of both lateral relations and informal networking on the extent of knowledge sharing between the marketing and accounting departments (MAKS). Finally, this study finds that organizational innovativeness partially mediates the MAKS–performance link, emphasizing the role of innovation in transforming knowledge to performance.